Auctions under Payoff Uncertainty: The Case with Heterogeneous Bidder-Aversion to Downside Risk - Audrey Hu; Liang Zou (Tinbergen Institute, 2008)
This paper characterizes the optimal first-price auction (FPA) and second-price auction (SPA) for selling rights, contracts, or licenses that involve ensuing payoff uncertainty for the winning bidder. The distribution of the random payoff is common knowledge, except that bidders have private degrees of aversion to downside-risk. In this model, the optimal FPA entails a lower reserve price, a higher expected revenue, and higher expected utilities for at least some or all bidders than the optimal SPA does, which suggests that FPA dominates SPA in terms of both allocative and Pareto efficiency. Increasing risk or risk aversion generally leads to lower equilibrium bids.
Keywords: D44; 330; auction; downside risk; risk aversion; payoff uncertainty; allocative efficiency; Pareto efficiency; Auktionstheorie; Risikoaversion; Zahlungsverhalten; Allokationseffizienz; Pareto-Optimum; Theorie